2016
DOI: 10.1684/epd.2016.0809
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric and Behavioural Disorders in Children with Epilepsy: an ILAE Task Force Report

Abstract: A subtle behavioural or cognitive manifestation of epilepsy can be defined in two ways. First, epileptiform discharges not presenting as obvious seizures may nevertheless affect cognition and/or behaviour. Second, the actual seizures may be obvious but the way they affect cognition or behaviour may not be. There is a growing body of evidence indicating that the epileptiform discharges in benign epilepsy with centrotemporal spikes can affect behaviour and cognition. The focal discharges in other forms of epilep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0
11

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(76 citation statements)
references
References 45 publications
1
64
0
11
Order By: Relevance
“…ADHD has proven to be very common in children with epilepsy. Reports estimate that 30% of children with epilepsy may meet criteria for ADHD, with some reports suggesting prevalence up to 80% (70)(71)(72). Both epilepsy and ADHD have problematic effects upon quality of life.…”
Section: Attention Deficit Hyperactivity Disorder (Adhd)mentioning
confidence: 99%
“…ADHD has proven to be very common in children with epilepsy. Reports estimate that 30% of children with epilepsy may meet criteria for ADHD, with some reports suggesting prevalence up to 80% (70)(71)(72). Both epilepsy and ADHD have problematic effects upon quality of life.…”
Section: Attention Deficit Hyperactivity Disorder (Adhd)mentioning
confidence: 99%
“…Interestingly, in WAG/Rij rats and CAE, behaviour and epilepsy could share common mechanisms [9,30,54]. Up to now, (see above) several drugs have been tested in this experimental model.…”
Section: Resultsmentioning
confidence: 96%
“…Therefore, this issue should be clarified in future studies. Interestingly, neuropsychiatric comorbidities can also occur in childhood absence epilepsy (CAE) that in the past was wrongly considered as a benign form of epilepsy [53][54][55]. Despite the underlying mechanisms involved in neuropsychiatric comorbidity in CAE remain still to be uncovered, it has been suggested that the same mechanisms leading to network abnormalities can also play a key role in the neuropsychiatric comorbidities onset in these patients [30].…”
Section: Wag/rij Rats and Neuropsychiatric Comorbiditiesmentioning
confidence: 99%
“…A retrospective study of 14 LKS children [21] has revealed that the 57% cases evidenced attentional or other behavioral problems, 5057% having deficits in auditory working memory and verbal memory. Academically, the majority had poor reading fluency and comprehension, and 50% exhibited difficulty with mathematics.…”
Section: Lks and Behavioral Disturbances/ Cognitive Impairmentsmentioning
confidence: 99%